PENGARUH KONSUMSI SHORT-FORM CONTENT TERHADAP RENTANG PERHATIAN MAHASISWA DALAM PENGGUNAAN MEDIA SOSIAL - Arindra Pasca Mauliddiana; Elviana Rohmah Rosyidatul ‘Ula; Taqiyyatul Azizah; Shabrina Nailah Lubis; Wiryo Nuryono; Devi Ratnasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of short-form content consumption on students’ attention span in social media usage. The rapid growth of platforms such as TikTok, Instagram Reels, and YouTube Shorts has shifted information consumption patterns toward faster, more instant, and repetitive formats. This research employs a literature review method by examining relevant studies to understand consumption patterns, attraction mechanisms through algorithms and reward systems, and their impacts on attention and academic activities. The findings indicate that excessive consumption of short-form content is associated with decreased ability to sustain attention, increased distraction, and ineffective digital multitasking habits. Furthermore, algorithmic systems and dopamine-based reward mechanisms reinforce user engagement, leading to compulsive usage behavior. These effects also influence academic activities, including increased procrastination and decreased learning quality. In conclusion, short-form content consumption significantly affects students’ attention span. This study highlights the importance of managing social media use and developing intervention strategies in guidance and counseling to minimize negative impacts on cognitive functions and academic performance.